Assessment of novel C-4 methylated tetraketide by HPLC-SPE-TT in saccharicola sp., an endophytic fungus in Eugenia Jambolana Lam - Borges, Maiara S. [UNESP]; Biasetto, Carolina R. [UNESP]; Chapla, Vanessa M.; Ebrahimi, Samad N.; Costa, Mayra F. [UNESP]; Bolzani, Vanderlan S. [UNESP]; Araujo, Angela R. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2019)
A new compound named methyl (6S,7S,2E,4E)-6,7-dihydroxy-4,6-dimethyl octanoate was isolated from Saccharicola sp. using high performance liquid chromatography-solid phase extraction-transfer tube (HPLC-SPE-TT), together with four known compounds, fusaric acid, trans-4-hydroxymellein, thymidine and adenosine. Saccharicola sp. was isolated from the stems of Eugenia jambolana Lam. (Myrtaceae) as endophytic fungus. The structure of this novel substance was established based on its spectroscopic data, including 1H and 13C nuclear magnetic resonance (NMR), 2D NMR techniques and high-resolution electrospray ionization mass spectrometry (HR-ESI-MS). This paper deals with the first report of its kind on this compound in Saccharicola sp.
Keywords: Endophytic fungus; Eugenia jambolana Lam; Saccharicola sp